Toxicological Exploration of Tapak Dara Catharanthus roseus as Bioinsecticide - Ahyanti, Mei (Jurnal Kesehatan, 2025)
Mosquito control efforts have been done physically, chemically, and through environmental management. However, the use of synthetic chemical insecticides has various negative impacts. Therefore, plant-based alternatives are a solution that needs to be developed. This study explores the toxicological potential of Catharanthus roseus as a botanical bioinsecticide. This systematic review study takes data from the literature in the form of published articles obtained via the internet from Google Scholar, Semantic Sholar, Garuda, PubMed, and Science Direct databases. The subjects of the study were 12 articles that focused on using Catharanthus roseus as a larvicide. The selected journals were eligible based on the study of LC50, zero value, and No Observed Adverse (NOA) of Catharanthus roseus plant extract against mosquito larvae. The data are presented in tabular form. Several studies provided different results regarding LC50 and zero value, but only 1 study reported on NOA. Further research is needed to improve data consistency, especially on LC50 values ​​and control effects, including against non-target organisms.